A platform for mapping reactive cysteines within the immunopeptidome - Chenlu Zhang; Chen Zhou; Assa Magassa; Xiaokang Jin; Deyu Fang; Xiaoyu Zhang (Nature Communications)
Abstract The major histocompatibility complex class I antigen presentation pathways play pivotal roles in orchestrating immune responses. Recent studies have begun to explore the therapeutic potential of cysteines within the immunopeptidome, such as the use of covalent ligands to generate haptenated peptide neoepitopes for immunotherapy. In this work, we report a platform for mapping reactive cysteines on MHC-I-bound peptide antigens. We develop cell-impermeable sulfonated maleimide probes capable of capturing reactive cysteines on these antigens. Using these probes in chemoproteomic experiments, we discover that cysteines on MHC-I-bound antigens exhibit various degrees of reactivity. Moreover, interferon-gamma stimulation enhances the reactivity of cysteines at position 8 of 9-mer MHC-I-bound antigens. Finally, we demonstrate that targeting reactive cysteines on MHC-I-bound antigens with a maleimide-conjugated Fc-binding cyclic peptide contributes to the induction of antibody-dependent cellular phagocytosis.